The truncated form of the Epstein-Barr virus latent-infection membrane protein expressed in virus replication does not transform rodent fibroblasts. - Wang, D (1988)
The gene encoding the Epstein-Barr virus membrane protein LMP, expressed in latent infection, is known to induce morphologic changes and some loss of contact inhibition in NIH 3T3 cells as well as profound loss of contact inhibition and of anchorage dependence in Rat-1 cells. Another form of LMP (D1LMP), deleted for the amino terminus and first four putative transmembrane domains of LMP, was recently shown to be expressed late in Epstein-Barr virus replication. We now demonstrate that D1LMP has no transformation-associated phenotypic effect in Rat-1 cells and does not significantly affect LMP-induced Rat-1 cell transformation. LMP activity and D1LMP inactivity in inducing anchorage-independent growth are not restricted to Rat-1 cells, but are also evident in BALB/c 3T3 cells. In both cell types, loss of contact inhibition and anchorage independence are acutely evident after LMP expression. Although newly transfected polyclonal Rat-1 or BALB/c cells have a lower agar cloning efficiency than established LMP-expressing clones, this is attributable, at least in part, to their lower average LMP expression, since among clones of transfected cells, higher cloning efficiencies correlated with higher levels of LMP. LMP is bound to the vimentin cytoskeletal network in rodent fibroblasts as it is in transformed lymphocytes, whereas D1LMP showed no detectable cytoskeletal binding, suggesting that cytoskeletal association may be integral to LMP-mediated cell transformation. LMP association with the cytoskeleton in latently infected, growth-transformed lymphocytes and LMP-transformed rodent fibroblasts, correlated with the lack of both rodent cell-transforming activity and cytoskeletal association of D1LMP supports working hypothesis that cytoskeletal association is important in LMP transforming activity.